CALCULATION FORMULAS FOR DETERMINING THE SPEED OF UNLOADING ENERGY WILLOW CUTTINGS FROM THE POINT OF VIEW OF HYDRODYNAMIC MULTIPHASE SYSTEMS - Yermakov , S.V.; Hutsol, T.D.; Mykhailova, L.M. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Numerous studies of the process of vaulting have established only some dependencies that explain the essence of this process. But today there is no single theory of leakage of bulk materials and cryptocurrency processes in the hopper, so the problem remains relevant. This work is the final of a series of works by the authors devoted to the construction of a mathematical model of the process of unloading cuttings from the slot hopper, so its purpose is to derive calculation formulas for the mass of cuttings by gravity unloading them from the slot hopper. The research is based on the known scientific methods of substantiation of the process of unloading bulk material from tanks, with the development of issues of solving the problems of basement formation and continuous pouring of the material. Such methods include the use of computational mathematics to build a mathematical model of the movement of cuttings and its processing In the article it is offered to consider gravitational unloading of cuttings of an energy willow from the point of view of hydrodynamic multiphase systems. According to this approach, the set of cuttings is considered as a pseudo-liquid, consisting of two phases: discrete (cuttings) and continuous (air). Taking each of these phases as a continuous medium, we can consider the unloading of cuttings as the motion of a viscous incompressible pseudo-liquid, the velocity field of which can be characterized by the Navier–Stokes equation. The result of the development is an algorithm for constructing a mathematical model of motion of such a pseudofluid and the transition to the calculated equations of motion with initial and boundary conditions, which will eventually lead to the possibility of theoretical analysis of the process of unloading cuttings from slot bunkers.